Heat transfer performance of non-circular coiled tubes - Research summary, challenges and directions - Kurnia , J.C.; Sasmito, A.P. (International Journal of Automotive and Mechanical Engineering, 2022)
Coiled tubes have been widely used in major industries due to their high heat transfer, ease of manufacturing and compactness. Numerous studies have been conducted experimentally and numerically to evaluate the heat transfer performance of coiled tubes. A majority of these studies were focused on circular tubes, while only limited studies were concerned on non-circular tubes. Recently, a series of computational studies have been conducted in our research group to investigate the flow characteristic and heat transfer performance of non-circular coiled tubes. Several key parameters affecting flow behavior and heat transfer performance have been evaluated and examined. The heat transfer performance is numerically evaluated and compared by utilizing the concept of Figure of Merit (FoM). The paper is intended to provide an essential summary of these numerical studies with the aim of providing a general overview of the advantage and drawbacks of non-circular coiled tubes in thermal engineering applications. Challenges and directions of the research will also be discussed. In general, it is revealed that heat transfer improvement in the coiled tube is followed by increasing pumping power. Moreover, with a more complex coiled geometry proposed, the processes of manufacturing the tube and creating the computational domain will become major issues in non-circular coiled tube studies. In addition, more studies on the application of coiled tubes used for heat exchanger and chemical reactor are expected to increase in the future, especially in the micro or nanoscale.